Whakamanahia Te mātauranga o te Māori: empowering Māori knowledge to support Aotearoa’s aquatic biological heritage - James Ataria; Melanie Mark‐Shadbolt; Aroha Te Pareake Mead; Kevin Prime; Jim Doherty; James Waiwai; Tohe Ashby; Simon Lambert; Gary Owen Garner (New Zealand Journal of Marine and Freshwater Research, 2018)
As Aotearoa New Zealand grapples with developing solutions to complex issues surrounding its unique freshwater and marine biological heritage, there is a growing recognition that mātauranga Māori can be ‘unlocked’ and used with great effect alongside western science. Examples where appropriate consideration and development of robust methodologies for the application of mātauranga Māori coexisting alongside western science are increasing. Unfortunately, despite the benefits that can be derived from this collaboration, the quality of engagement is not always satisfactory often due to poor interpersonal relationships and misidentification of the knowledge holders. By providing an appropriately historical context, this article is able to consider the critical issues now facing mātauranga and the Māori knowledge holders today, and fundamental requirements that will empower application of this knowledge within bio‐heritage management. We consider how the development of a methodology between mātauranga Māori holders and potential end‐users might contribute to improved outcomes for Aotearoa’s biological heritage.